Konseling Religi dalam Upaya Menemukan Kebermaknaan Hidup Remaja Korban Broken Home - Rois Nafi'ul Umam; Maemonah Maemonah (Universitas Mathla'ul Anwar Banten, 2021)
RELIGIOUS COUNSELING IN AN EFFFORT TO FIND A MEANINGFULL LIFE FOR TEENAGER VICTIMS OF BROKEN HOME. The purpose of this research is to explain the phenomenon of teenage victims of broken home in their efforts to find meaning in life through religious counseling services. The type of this research is phenomenological qualitative. Data collection techniques were carried out by observation and interviews. The data analysis technique used intra-case and inter-case analysis. The results showed that the reasons for these adolescents to attend religious counseling in order to find meaning in their lives included; forgetting the disappointments they face, finding wisdom from the problems that occur, finding meaning in life, and preparing for a new life. Religious counseling is carried out through several activities such as reading the Koran, listening to lectures, reading Islamic and motivational books.